Process for the preparation of an anti-aging cable sheath material and use thereof

CN122917523APending Publication Date: 2026-10-16HEBEI QISU PLASTIC PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611363401.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种抗老化的电缆护套材料制备方法及其应用,解决现有电缆护套材料无法应对铜离子催化氧化、纳米填料与抗氧剂无化学关联导致协同效应不足、小分子抗老化助剂易迁移挥发导致长期防护效果衰减的技术问题

Benefits of technology

1、本发明通过在纳米杂化体表面接枝Schiff碱结构实现铜离子螯合失活,消除了电缆护套特有的金属催化氧化加速源,热老化后铜离子含量仅为8.2μg/g,较未功能化纳米填料体系降低77%。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of high polymer cable materials, in particular to a preparation method and application of an anti-aging cable sheath material, wherein 100 parts of polyether type thermoplastic polyurethane have a Shore hardness of 80A to 90A, a melting index of 15 to 35 g / 10 min under a load of 2.16 kg at 200 DEG C; 2 to 6 parts of Schiff base functionalized ZnO / ZnAl-LDH hierarchical nanohybrids, 0.3 to 0.8 parts of hindered phenolic antioxidants, 0.3 to 0.8 parts of phosphite antioxidants, 0.5 to 1.5 parts of benzotriazole ultraviolet absorbers, 1 to 3 parts of carbon black with a particle size of 20 to 40 nm, and 0.3 to 0.8 parts of zinc stearate are used. The copper ion chelation inactivation is realized by grafting a Schiff base structure on the surface of the nanohybrid, the metal-catalyzed oxidation accelerating source specific to the cable sheath is eliminated, and the copper ion content after heat aging is only 8.2 mu g / g, which is reduced by 77% compared with the non-functionalized nanofiller system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer cable materials technology, specifically to a method for preparing an anti-aging cable sheath material and its application. Background Technology

[0002] The cable sheath is the outermost protective structure of a cable. Long-term exposure to harsh environments such as sunlight, high temperatures, and humidity makes its aging and failure a primary cause of cable failures. Cable sheath aging mainly includes four forms: thermo-oxidative aging, ultraviolet light aging, metal-catalyzed oxidation, and wet-water hydrolysis. Among these, metal-catalyzed oxidation is a unique aging mechanism for cable sheaths: copper ions in the copper conductor migrate to the sheath layer under high temperature and electric field conditions. Cu ions react with peroxides to generate Cu ions and alkoxy radicals, greatly accelerating the oxidative degradation of the polymer. Therefore, copper ion deactivation is a key issue that needs to be addressed in the anti-aging process of cable sheaths.

[0003] Existing patent CN103897231B discloses a heat-resistant and anti-aging cable sheath material, which uses polystable nitrile rubber and hydrogenated nitrile rubber as the matrix and adds organic nano-montmorillonite and silica for reinforcement. This method has good heat resistance, but does not involve the copper ion deactivation mechanism. The copper conductor migration ions will continue to catalyze oxidation and degradation.

[0004] Existing patent CN108003602B discloses a thermoplastic polyurethane composite material for cable and optical cable sheaths, which uses TPU to be composited with continuous long fibers and adds hindered phenol and phosphite antioxidants. This method has excellent mechanical properties, but the antioxidants are small molecules that are easy to migrate and volatilize, and the protective effect decreases with long-term aging. In addition, it does not solve the problem of copper ion catalytic oxidation.

[0005] Existing anti-aging cable sheath technologies have the following problems: the antioxidant system is only a traditional combination of hindered phenol and phosphite, which cannot cope with the unique aging mechanism of copper ion catalytic oxidation in cables. After thermal aging, copper ions accumulate in large quantities in the sheath, accelerating degradation; inorganic nanofillers and antioxidants are added independently, and there is no chemical connection between the two. The physical barrier effect of nanofillers and the chemical protective effect of antioxidants cannot be synergistically amplified; both UV absorbers and antioxidants are small molecules, which are prone to migrate to the sheath surface and volatilize during long-term high-temperature service, resulting in a sharp decline in anti-aging performance over time. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing anti-aging cable sheath materials and their application, solving the technical problems that existing cable sheath materials cannot cope with the catalytic oxidation of copper ions, the lack of chemical correlation between nanofillers and antioxidants leading to insufficient synergistic effect, and the easy migration and volatilization of small molecule anti-aging additives leading to long-term attenuation of protective effect.

[0007] A further object of the present invention is to provide an anti-aging cable sheath material, prepared from the following raw materials in parts by weight: 100 parts of polyether-type thermoplastic polyurethane, Shore hardness 80A to 90A, melt index 15 to 35 g / 10min at 200℃ and 2.16 kg load; Two to six parts of Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids were prepared, wherein the Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids were prepared using ZnAl layered double hydroxide with a Zn to Al molar ratio of 3:1 as a support, ZnO nanoparticles were loaded on the surface of the support, and the surface of the support was modified with γ-aminopropyltriethoxysilane and then reacted with salicylaldehyde to form a Schiff base structure. Hindered phenolic antioxidants 0.3 to 0.8 parts; phosphite antioxidants 0.3 to 0.8 parts; benzotriazole UV absorbers 0.5 to 1.5 parts; carbon black 1 to 3 parts, particle size 20 to 40 nm; zinc stearate 0.3 to 0.8 parts.

[0008] Preferably, the preparation method of the Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrid includes the following steps: Step A: Dissolve zinc nitrate and aluminum nitrate in deionized water at a Zn to Al molar ratio of 3:1 to prepare a mixed salt solution. Dissolve NaOH and Na2CO3 in deionized water to prepare an alkaline solution. Add the mixed salt solution and the alkaline solution dropwise to the deionized water simultaneously, maintaining a temperature of 60℃ and a pH of 10.0 to 10.5. After the addition is complete, age the solution at 60℃ for 16 to 20 hours. Filter and wash the solution until the pH of the filtrate is less than 8, and dry it at 80℃ for 10 to 14 hours to obtain ZnAl-LDH. Step B: Disperse ZnAl-LDH in a mixed solvent of ethanol and water, with a volume ratio of ethanol to water of 4:1. Add zinc acetate dihydrate, with a mass ratio of zinc acetate dihydrate to ZnAl-LDH of 1:2 to 1:4. Stir at 70°C for 1 to 2 hours, then add NaOH ethanol solution dropwise to make the molar ratio of Zn to OH 1:2. Continue stirring for 2 to 4 hours, filter, and then heat-treat at 150°C for 2 hours to obtain ZnO / ZnAl-LDH. Step C: Disperse ZnO / ZnAl-LDH in a mixed solvent of ethanol and water, with a volume ratio of ethanol to water of 95:5. Add γ-aminopropyltriethoxysilane, with the amount of γ-aminopropyltriethoxysilane being 2 to 5% of the mass of ZnO / ZnAl-LDH. Stir at 60°C for 3 to 5 hours. Filter, wash, and dry to obtain amino-modified ZnO / ZnAl-LDH. Step D: Disperse amino-modified ZnO / ZnAl-LDH in anhydrous ethanol, add salicylaldehyde, the mass ratio of salicylaldehyde to amino-modified ZnO / ZnAl-LDH is 1:8 to 1:12, stir at 50℃ for 5 to 7 h, filter and wash, and then vacuum dry at 60℃ for 6 to 10 h to obtain Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids.

[0009] Preferably, the polyether-type thermoplastic polyurethane is of the polytetrahydrofuran ether diol type, with a number average molecular weight of 80,000 to 120,000.

[0010] Preferably, the hindered phenolic antioxidant is β-3,5-di-tert-butyl-4-hydroxyphenylpropionate n-octadecyl alcohol ester, the phosphite antioxidant is tris-2,4-di-tert-butylphenyl phosphite ester, and the benzotriazole UV absorber is 2-2H-benzotriazole-2-yl-4,6-di-tert-pentylphenol.

[0011] Preferably, the anti-aging cable sheath material retains a tensile strength of ≥83% and an elongation at break of ≥80% after heat aging at 135℃ for 168 hours; retains a tensile strength of ≥86% and an elongation at break of ≥82% after UV aging for 500 hours; and has a copper ion content of ≤15μg / g after heat aging at 135℃ for 168 hours.

[0012] A method for preparing the anti-aging cable sheath material includes the following steps: Step 1: Weigh out the following components according to the specified ratio: polyether thermoplastic polyurethane, Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid, hindered phenolic antioxidant, phosphite antioxidant, benzotriazole UV absorber, carbon black, and zinc stearate. Dry the polyether thermoplastic polyurethane at 80 to 90°C for 3 to 4 hours, and dry the Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid and carbon black at 100 to 110°C for 2 to 3 hours. Step 2: Add the dried polyether thermoplastic polyurethane, Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid, carbon black and zinc stearate into a high-speed mixer and mix at 80 to 90°C and 600 to 800 r / min for 8 to 12 minutes. Then add hindered phenolic antioxidants, phosphite antioxidants and benzotriazole UV absorbers and continue mixing for 5 to 8 minutes to obtain the initial mixture. Step 3: Add the initial mixture to a twin-screw extruder for melt extrusion granulation. The temperature of the twin-screw extruder is 170 to 180℃ in zone 1, 180 to 190℃ in zone 2, 185 to 195℃ in zone 3, 180 to 190℃ in zone 4, and 175 to 185℃ at the die head. The screw speed is 250 to 350 r / min. After water cooling and pelletizing, cable sheath material granules are obtained. Step 4: After drying the cable sheath material granules at 80 to 90°C for 2 to 3 hours, add them to an extruder and extrude them onto the outer surface of the cable conductor at an extrusion temperature of 175 to 195°C. After cooling and shaping, an anti-aging cable sheath is obtained.

[0013] Preferably, the Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nanohybrid described in step one is prepared by the following method: zinc nitrate and aluminum nitrate are dissolved in deionized water at a Zn to Al molar ratio of 3:1 to prepare a mixed salt solution; NaOH and Na2CO3 are dissolved in deionized water to prepare an alkali solution; the mixed salt solution and the alkali solution are simultaneously added dropwise to deionized water while maintaining a temperature of 60°C and a pH of 10.0 to 10.5; after the addition is complete, the solution is aged at 60°C for 16 to 20 hours; the solution is filtered and washed until the pH of the filtrate is less than 8; and then dried at 80°C for 10 to 14 hours to obtain ZnAl-LDH. ZnAl-LDH was dispersed in a mixed solvent of ethanol and water, zinc acetate dihydrate was added, and the mixture was stirred at 70°C for 1 to 2 hours. Then, NaOH ethanol solution was added dropwise, and the mixture was stirred for another 2 to 4 hours. After filtration, the mixture was heat-treated at 150°C for 2 hours to obtain ZnO / ZnAl-LDH. ZnO / ZnAl-LDH was dispersed in a mixed solvent of ethanol and water, γ-aminopropyltriethoxysilane was added, and the mixture was stirred at 60°C for 3 to 5 hours. After filtration, washing, and drying, amino-modified ZnO / ZnAl-LDH was obtained. Amino-modified ZnO / ZnAl-LDH was dispersed in anhydrous ethanol, salicylaldehyde was added, and the mixture was stirred at 50°C for 5 to 7 hours. After filtration, washing, and vacuum drying at 60°C for 6 to 10 hours, Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids were obtained.

[0014] Preferably, in step three, the length-to-diameter ratio of the twin-screw extruder is 40:1 to 48:1, and each section of the screw is equipped with kneading blocks to improve the dispersion uniformity of Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids in the polyether-type thermoplastic polyurethane matrix.

[0015] A cable comprising a conductor and a sheath covering the outer surface of the conductor, the sheath being made of an anti-aging cable sheath material.

[0016] Preferably, the cable is used in outdoor wiring scenarios in photovoltaic power stations, wind farms or industrial plants, with a long-term operating temperature of -40 to 105°C and a service life of ≥25 years.

[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention achieves copper ion chelation and deactivation by grafting Schiff base structures onto the surface of the nano-hybrid, eliminating the metal catalytic oxidation acceleration source unique to cable sheaths. After thermal aging, the copper ion content is only 8.2 μg / g, which is 77% lower than that of the unfunctionalized nanofiller system.

[0018] 2. This invention integrates four protections—Schiff alkali copper ion deactivation, ZnO peroxide decomposition, LDH physical barrier, and acid product absorption—into a single nano-hybrid, avoiding the problems of poor compatibility and functional conflict caused by the independent addition of multiple additives. The tensile strength retention rate after thermal aging reaches 88%.

[0019] 3. This invention anchors the Schiff base to the surface of the nano-hybrid through covalent bonds, overcoming the defect of small molecule copper ion deactivators migrating and volatilizing at high temperatures. The long-term aging protection effect is stable, and the tensile strength retention rate is still 91% after 500h of ultraviolet aging.

[0020] 4. This invention uses polyether-type TPU as the matrix, which has better hydrolysis resistance, low-temperature flexibility and environmental friendliness compared with PVC and rubber-based cable sheath materials. In addition, the Schiff alkali-functionalized nano-hybrid has good interfacial compatibility with the TPU matrix.

[0021] 5. The preparation method of the present invention has controllable process and reasonable step connection. The Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nanohybrid is uniformly dispersed in TPU matrix, which is suitable for industrial-scale production. Detailed Implementation

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] This invention constructs a multi-synergistic anti-aging protection system in a polyether-type TPU matrix by Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrid, achieving simultaneous effects of copper ion chelation inactivation, peroxide catalytic decomposition, oxygen / moisture physical barrier, and absorption of acidic degradation products.

[0024] Specifically, the cable sheath is in direct contact with the copper conductor. During long-term operation, copper ions migrate and diffuse along the concentration gradient into the sheath layer. Monovalent copper ions react with the polymer peroxide ROOH to generate divalent copper ions and alkoxy radicals RO. The divalent copper ions then react with ROOH to generate monovalent copper ions and peroxy radicals ROO. Copper ions cycle between the two valence states, continuously generating new free radicals, causing the oxidation chain reaction to accelerate exponentially, thus accelerating the oxidation rate exponentially. Traditional hindered phenol / phosphite antioxidant systems can only capture free radicals and decompose peroxides, but cannot eliminate the catalytic effect of copper ions themselves. Therefore, copper ions continuously generate new free radicals, causing the antioxidant to be rapidly depleted.

[0025] In this invention, the imine bond and phenolic hydroxyl group in the Schiff base structure grafted onto the surface of the nano-hybrid can form a stable five-membered chelate ring with copper ions, firmly fixing the Cu ions to the surface of the hybrid and eliminating the catalytic activity of copper ions.

[0026] Unlike the independent addition of small-molecule copper ion deactivators, this invention anchors the Schiff base to the surface of the nano-hybrid, avoiding the migration and volatilization of the deactivator itself at high temperatures, thus achieving long-term stability of the copper ion deactivation function. This mechanism can be confirmed by comparing the copper ion content data after thermal aging of Example 1 and Comparative Example 2.

[0027] In terms of peroxide decomposition, ZnO nanoparticles supported on the surface of the hybrid exhibit peroxide catalytic decomposition activity.

[0028] The Zn ion sites on the ZnO surface can adsorb peroxide ROOH and cause it to undergo heterolytic decomposition, generating stable alcohol ROH instead of free radicals, thereby interrupting the propagation path of the oxidation chain reaction.

[0029] ZnO forms a secondary protection with hindered phenol / phosphite antioxidants: hindered phenols capture initial free radicals R and ROO as the first level of protection, phosphites reduce ROOH to ROH as the second level of protection, and ZnO catalytically decomposes the residual ROOH that escapes the first two levels of protection as the third level of protection. The three levels of protection intercept each other, preventing the free radical chain reaction from continuing to propagate.

[0030] This mechanism can be confirmed by comparing the tensile strength retention rate after thermal aging of Example 1 and Comparative Example 3.

[0031] In terms of physical barrier properties, ZnAl-LDH exhibits a typical layered structure, with its layers stacked face-to-face to form an oriented barrier structure within the TPU matrix. The diffusion of oxygen and water molecules within the TPU matrix must bypass the LDH layers, undergoing a tortuous diffusion path, effectively extending the time it takes for oxygen and moisture to reach the interior of the material.

[0032] Simultaneously, CO3 ions between the LDH layers can undergo ion exchange reactions with acidic products such as formic acid and acetic acid generated from the thermal oxidative degradation of TPU, fixing the acidic products within the LDH layers and preventing them from further catalyzing the hydrolysis and breakage of urethane bonds in the TPU backbone. This mechanism can be confirmed by comparing the elongation at break retention data after wet heat aging between Example 1 and Comparative Example 5.

[0033] The aforementioned multiple protection mechanisms exhibit a strict synergistic dependency: Schiff base chelation of copper ions eliminates the accelerating source of metal-catalyzed oxidation, reducing the peroxide load faced by ZnO and antioxidants to a manageable level; ZnO catalytic decomposition of peroxides reduces the rate of free radical generation, slowing down the consumption rate of hindered phenol / phosphite antioxidants and extending the effective protection time of antioxidants; LDH physical barrier slows down the penetration of oxygen and moisture, reducing the peroxide generation rate at the source, further alleviating the workload of ZnO and antioxidants; LDH absorption of acidic products prevents acid-catalyzed hydrolysis from damaging the TPU backbone, maintaining the integrity of the matrix and ensuring that LDH sheets maintain their orientation and do not collapse.

[0034] The four elements form a positive feedback loop: weakening any one link will increase the load on other links and accelerate failure. This synergistic effect can be quantitatively confirmed by the performance differences between Example 1 and the comparative examples: when Schiff base is missing, the copper ion content increases from 8.2 μg / g to 35.2 μg / g, an increase of 329%, and the heat aging tensile strength retention rate decreases from 88% to 75%, a decrease of 15%; when ZnO is missing, the heat aging tensile strength retention rate decreases from 88% to 72%, a decrease of 18%; when LDH layered structure is missing, the heat aging tensile strength retention rate decreases from 88% to 73%, a decrease of 17%; the absence of any one of the three elements leads to a significant decrease in the overall protective effect.

[0035] Raw material source: Polyether-type thermoplastic polyurethane: polytetrahydrofuran ether diol type, Shore hardness 85A, melt index 25g / 10min at 200℃ and 2.16kg load, number average molecular weight 95000, Covestro Desmopan 385E; Zinc nitrate hexahydrate: analytical grade, purity ≥ 99%, Sinopharm Chemical Reagent Co., Ltd. Aluminum nitrate nonahydrate: analytical grade, purity ≥ 99%, Sinopharm Chemical Reagent Co., Ltd. NaOH: Analytical grade, purity ≥ 96%, Shandong Haihua Group Co., Ltd. Na2CO3: Analytical grade, purity ≥ 99.8%, Sinopharm Chemical Reagent Co., Ltd. Zinc acetate dihydrate: analytical grade, purity ≥ 99%, Sinopharm Chemical Reagent Co., Ltd. γ-aminopropyltriethoxysilane: Industrial grade, purity ≥ 97%, Nanjing Shuguang Silane Chemical Co., Ltd.; Salicylaldehyde: Analytical grade, purity ≥ 99%, Sinopharm Chemical Reagent Co., Ltd. β-3,5-Di-tert-butyl-4-hydroxyphenylpropionate n-octadecyl alcohol ester: industrial grade, purity greater than or equal to 98%, i.e. antioxidant 1076, BASF. Tris(2,4-di-tert-butylphenyl) phosphite: Industrial grade, purity greater than or equal to 98%, i.e., antioxidant 168, BASF. 2-2H-benzotriazol-2-yl-4,6-di-tert-pentylphenol: Industrial grade, purity greater than or equal to 97%, i.e., UV absorber UV-328, BASF Tinuvin 328; Carbon black N330: Particle size 25 to 35 nm, oil absorption value 80 to 100 g / kg, Cabot Corporation; Zinc stearate: Industrial grade, zinc content 10 to 11%, Dongguan Hanwei New Materials Technology Co., Ltd. Example

[0036] Raw material formula: 100 parts by weight of polyether-type thermoplastic polyurethane, 4 parts by weight of Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid, 0.5 parts by weight of antioxidant 1076, 0.5 parts by weight of antioxidant 168, 1.0 part by weight of UV-328, 2.0 parts by weight of carbon black N330, and 0.5 parts by weight of zinc stearate.

[0037] Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrid preparation: Step A: Dissolve 0.15 mol zinc nitrate hexahydrate and 0.05 mol aluminum nitrate nonahydrate in 200 mL of deionized water to prepare a mixed salt solution. Dissolve 0.4 mol NaOH and 0.1 mol Na2CO3 in 200 mL of deionized water to prepare an alkaline solution. Add the mixed salt solution and the alkaline solution dropwise at a rate of 2 mL / min to a four-necked flask containing 100 mL of deionized water. Maintain the temperature at 60 °C and the pH value between 10.0 and 10.5. After the addition is complete, age at 60 °C for 18 h. Filter and wash with deionized water until the pH of the filtrate is 7.5. Dry in an 80 °C forced-air drying oven for 12 h to obtain ZnAl-LDH white powder.

[0038] Step B: Disperse 10g of ZnAl-LDH in a mixed solvent of 400mL ethanol and water (volume ratio of ethanol to water is 4:1), sonicate for 30min, add 3.33g of zinc acetate dihydrate dissolved in 50mL of ethanol, stir at 70℃ for 1.5h, then add 20mL of 1mol / L NaOH ethanol solution, continue stirring for 3h, filter and wash three times with ethanol, place the filter cake in a muffle furnace and heat treat at 150℃ for 2h to obtain a light yellow ZnO / ZnAl-LDH powder.

[0039] Step C: Take 5g of ZnO / ZnAl-LDH and disperse it in 200mL of a mixed solvent of ethanol and water, with a volume ratio of ethanol to water of 95:5. Sonicate the mixture for 15min, add 0.15g of γ-aminopropyltriethoxysilane, stir at 60℃ for 4h, filter and wash with ethanol 3 times, and dry at 80℃ for 6h to obtain amino-modified ZnO / ZnAl-LDH.

[0040] Step D: Take 5g of amino-modified ZnO / ZnAl-LDH and disperse it in 150mL of anhydrous ethanol. Sonicate the dispersion for 15min, add 0.5g of salicylaldehyde, stir at 50℃ for 6h, filter and wash three times with anhydrous ethanol to remove unreacted salicylaldehyde, and dry in a vacuum drying oven at 60℃ for 8h to obtain Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids, which are yellow powders.

[0041] Preparation process: Step 1: Weigh each raw material according to the ratio, dry the polyether-type thermoplastic polyurethane at 85℃ for 3.5h, and dry the Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid and carbon black N330 at 105℃ for 2.5h.

[0042] Step 2: Add the dried polyether thermoplastic polyurethane, Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid, carbon black N330, and zinc stearate to a high-speed mixer and mix at 85°C and 700 r / min for 10 min. Then add antioxidant 1076, antioxidant 168, and UV-328 and continue mixing for 6 min to obtain the initial mixture.

[0043] Step 3: Add the initial mixture to a co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 for melt extrusion granulation. The temperatures in zones 1, 2, 3, and 4 are 185°C, and the die head temperature is 180°C. The screw speed is 300 r / min. After water cooling, the material is granulated to obtain cable sheath material granules.

[0044] Step 4: After drying the granules at 85℃ for 2.5 hours, add them to a single-screw extruder and extrude them to a thickness of 2.5 mm. 2The outer surface of the tin-plated copper conductor with a cross-sectional area is extruded at a temperature of 185℃ and then water-cooled to form an anti-aging cable sheath with a thickness of 0.8mm. Example

[0045] Raw material formula: 100 parts by weight of polyether-type thermoplastic polyurethane, 2 parts by weight of Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid, 0.3 parts by weight of antioxidant 1076, 0.3 parts by weight of antioxidant 168, 0.5 parts by weight of UV-328, 1.0 part by weight of carbon black N330, and 0.3 parts by weight of zinc stearate.

[0046] The preparation process is the same as in Example 1, but in step B, the mass ratio of zinc acetate dihydrate to ZnAl-LDH is 1:4, and in step D, the mass ratio of salicylaldehyde to amino-modified ZnO / ZnAl-LDH is 1:12. Example

[0047] Raw material formula: 100 parts by weight of polyether-type thermoplastic polyurethane, 6 parts by weight of Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid, 0.8 parts by weight of antioxidant 1076, 0.8 parts by weight of antioxidant 168, 1.5 parts by weight of UV-328, 3.0 parts by weight of carbon black N330, and 0.8 parts by weight of zinc stearate.

[0048] The preparation process is the same as in Example 1, but in step B, the mass ratio of zinc acetate dihydrate to ZnAl-LDH is 1:2, and in step D, the mass ratio of salicylaldehyde to amino-modified ZnO / ZnAl-LDH is 1:8.

[0049] Comparative Example 1: This comparative example does not use Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids.

[0050] Raw material formula: 100 parts by weight of polyether thermoplastic polyurethane, 4 parts by weight of ordinary nano ZnO, 0.5 parts by weight of antioxidant 1076, 0.5 parts by weight of antioxidant 168, 1.0 part by weight of UV-328, 2.0 parts by weight of carbon black N330, and 0.5 parts by weight of zinc stearate.

[0051] Ordinary nano-ZnO particles have a diameter of 30 to 50 nm and a specific surface area of ​​15 to 25 m². 2 / g, purchased from Shanghai Jinghua Chemical Co., Ltd.

[0052] The preparation process is the same as in Example 1.

[0053] Comparative Example 2: This comparative example uses unfunctionalized Schiff base ZnO / ZnAl-LDH instead of Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids.

[0054] The raw material formulation is the same as in Example 1, but the Schiff base-functionalized ZnO / ZnAl-LDH is replaced with an equal amount of unfunctionalized ZnO / ZnAl-LDH, that is, the salicylaldehyde reaction in step D is omitted.

[0055] The remaining steps are the same as in Example 1.

[0056] Comparative Example 3: This comparative example uses a nanohybrid that functionalizes LDH with only Schiff base and does not contain ZnO.

[0057] The raw material formulation is the same as in Example 1, but Schiff alkali-functionalized ZnO / ZnAl-LDH is replaced with Schiff alkali-functionalized LDH, that is, the ZnO loading in step B is omitted.

[0058] The remaining steps are the same as in Example 1.

[0059] Comparative Example 4: This comparative example uses a traditional antioxidant compounding scheme without adding any nano-hybrids.

[0060] Raw material formula: 100 parts by weight of polyether thermoplastic polyurethane, 1.0 part by weight of antioxidant 1076, 1.0 part by weight of antioxidant 168, 1.0 part by weight of UV-328, 2.0 parts by weight of carbon black N330, and 0.5 parts by weight of zinc stearate.

[0061] The preparation process is the same as in Example 1.

[0062] Comparative Example 5: This comparative example uses a simple physical mixture of ZnO and LDH to replace the hierarchical nanohybrid.

[0063] The raw material formulation is the same as in Example 1, but the Schiff alkali-functionalized ZnO / ZnAl-LDH is replaced with a simple physical mixture of 2 parts by mass of ordinary ZnAl-LDH, 2 parts by mass of ordinary nano ZnO, and 0.4 parts by mass of salicylaldehyde.

[0064] The ordinary ZnAl-LDH has a Zn to Al molar ratio of 3:1 and a d001 spacing of 0.89 nm, and was purchased from Jinan Henghua Chemical Co., Ltd.; the ordinary nano ZnO has a particle size of 30 to 50 nm and a specific surface area of ​​15 to 25 m². 2 / g, purchased from Shanghai Jinghua Chemical Co., Ltd.; salicylaldehyde purity greater than or equal to 99%, purchased from Sinopharm Chemical Reagent Co., Ltd.

[0065] The preparation process is the same as in Example 1.

[0066] Comparative Example 6: This comparative example describes a scheme in which antioxidants are loaded onto the surface of nano-silica and then copper ion deactivators are added.

[0067] Raw material formula: 100 parts by weight of polyether thermoplastic polyurethane, 4 parts by weight of antioxidant-supported nano-SiO2, 0.5 parts by weight of benzotriazole copper ion deactivator, 0.5 parts by weight of antioxidant 168, 1.0 part by weight of UV-328, 2.0 parts by weight of carbon black N330, and 0.5 parts by weight of zinc stearate.

[0068] The preparation method of antioxidant-supported nano-SiO2 is as follows: 10g of nano-SiO2 was dispersed in 200mL of anhydrous ethanol. The nano-SiO2 particles had a diameter of 20 to 40nm and a specific surface area of ​​150 to 200m². 2 / g, Evonik Aerosil 200, add 0.5g γ-glycidyl etheroxypropyltrimethoxysilane, stir at 70℃ for 4h, filter, wash and dry to obtain silane-modified nano-SiO2, then disperse it in 100mL toluene, add 2g antioxidant 1076, reflux at 110℃ for 6h, filter and wash with toluene and ethanol successively, vacuum dry at 80℃ for 8h to obtain antioxidant-supported nano-SiO2, antioxidant loading is 12% by mass.

[0069] The copper ion deactivator for benzotriazole is 1H-benzotriazole with a purity of ≥99%, purchased from Sinopharm Chemical Reagent Co., Ltd.

[0070] The preparation process is the same as in Example 1.

[0071] Comparative Example 7: This comparative example describes a scheme for blending Schiff base molecules with ZnO and LDH.

[0072] Raw material formula: 100 parts by weight of polyether thermoplastic polyurethane, 1 part by weight of ordinary nano ZnO2, 1 part by weight of ordinary ZnAl-LDH2, 0.5 parts by weight of bis(salicylic acid) ethylenediamine Schiff base, 0.5 parts by weight of antioxidant 1076, 0.5 parts by weight of antioxidant 168, 1.0 part by weight of UV-328, 2.0 parts by weight of carbon black N330, and 0.5 parts by weight of zinc stearate.

[0073] The purity of the disalicylaldehyde ethylenediamine Schiff base was greater than or equal to 98%, and it was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0074] The preparation process is the same as in Example 1.

[0075] To enable those skilled in the art to fully and clearly understand and reproduce the technical solution of this invention, and to fully implement the requirements of patent disclosure, the following supplementary explanations are provided regarding the definitions of key terms, missing parameters in the preparation process, criteria for determining service life, and compatibility with testing standards: The Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nanohybrid described in this invention is a two-level structured nanocomposite powder. The hierarchical structure specifically refers to the material's hierarchical structural design. The first-level structure is a ZnAl layered double hydroxide (ZnAl-LDH) sheet carrier with a Zn to Al molar ratio of 3:1. It relies on the layered structure to achieve physical barrier of oxygen and water vapor and adsorption of acidic degradation products. The second-level structure consists of ZnO nanoparticles uniformly loaded on the surface of ZnAl-LDH sheets, which enable the catalytic decomposition of organic peroxides. Then, through silane coupling agent grafting modification, salicylaldehyde-type Schiff base functional groups are covalently bonded to the surface of the composite powder. The Schiff base structure is used to chelate and passivate copper ions. The superposition of the two-level structures combined with surface functionalization modification constitutes the hierarchical nano-hybrid system unique to this invention.

[0076] For the preparation process of Schiff's alkali-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids, key limiting parameters for the entire process are supplemented to ensure stable and repeatable implementation of the process: In step A, during the preparation of ZnAl-LDH, the total molar concentration of the zinc nitrate-aluminum nitrate mixed salt solution is controlled at 0.8-1.2 mol / L, the total molar concentration of the NaOH-Na2CO3 mixed alkali solution is controlled at 1.5-2.0 mol / L, and the simultaneous dropping rate of the mixed salt solution and the alkali solution is 1-3 mL / min. In each reaction step (B, C, D), the solid-liquid mass ratio of the powder to the mixed solvent / anhydrous ethanol is uniformly controlled at 1:30-1:50 to ensure that the nanopowder is fully dispersed and the reaction proceeds uniformly. In step B, NaOH ethanol solution is added dropwise to allow Zn to react with OH-. - The molar ratio is 1:2, and the calculation basis for Zn element is limited to the zinc element dissociated from zinc acetate dihydrate in the system, excluding the zinc element inherent in the ZnAl-LDH support. The stoichiometric ratio of the precipitation reaction is strictly matched to ensure the directional loading effect of ZnO.

[0077] The technical feature of the cable product of this invention, with a long service life of ≥25 years, is explained in conjunction with the aging theory of polymer materials and the life assessment method of the cable industry: This invention employs 135℃ high-temperature forced ventilation thermal aging and UVA-340 ultraviolet accelerated aging to conduct accelerated life tests. Based on the Arrhenius rate equation for the thermo-oxidative aging of polymer materials, the material aging rate is exponentially correlated with the ambient temperature.

[0078] Based on the mechanical properties and copper ion content decay data obtained from the 135℃, 168h thermal aging and 500h UV aging of this invention, and combined with the actual operating conditions of outdoor wiring in photovoltaic power stations, wind farms, and industrial plants (long-term operating temperature -40℃ to 105℃, natural light, diurnal temperature variation, and humid environment), calculations were performed according to the accelerated aging life extrapolation model commonly used in the power cable industry. Simultaneously, this invention anchors the Schiff base to the surface of the nano-hybrid through covalent bonds, completely solving the problems of high-temperature migration and volatilization failure of small molecule additives. The quadruple anti-aging protection system can function stably for a long time. Based on comprehensive calculations, the continuous safe service life of the cable of this invention in the target outdoor application scenario is no less than 25 years. This conclusion is supported by accelerated aging test data and industry-standard life extrapolation theory.

[0079] The original standard GB / T2951.12-2008 cited in the thermal aging test of this invention is a special standard for polyolefin cable materials. However, since the matrix of this invention is polyether-type thermoplastic polyurethane, the formal performance testing uniformly adopts GB / T2951.41-2020 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Cables - Part 41: Special Methods for Polyurethane Elastomer Mixtures". The thermal aging test conditions of 135℃ and 168h, the sample treatment method, and the performance testing process set in this invention all meet the national standard requirements for polyurethane cable materials.

[0080] Performance testing and results analysis: (1) Tensile strength and elongation at break test: Performed in accordance with GB / T1040.2-2022, using type 1A dumbbell-shaped specimen, gauge length 50mm, tensile rate 500mm / min, temperature 23℃.

[0081] (2) Thermal aging test: The test shall be carried out in accordance with GB / T2951.12-2008. The sample shall be placed in a forced ventilation aging chamber at 135℃ for 168h and then taken out. After being placed at room temperature for 16h, the tensile properties shall be tested and the retention rate shall be calculated.

[0082] (3) Ultraviolet aging test: Performed in accordance with GB / T16422.3-2022, using UVA-340 lamp tubes, with an irradiance of 0.89W / m. 2 The standard temperature for blackening is 60℃, the condensation temperature is 50℃, and the cycle consists of 4 hours of irradiation followed by 4 hours of condensation, for a total of 500 hours.

[0083] (4) Copper ion content test: The aged sample was digested with nitric acid and the copper content was determined by an inductively coupled plasma atomic emission spectrometer ICAP7400.

[0084] (5) Shore hardness test: Performed in accordance with GB / T531.1-2008, Shore A type.

[0085] Each group of samples was tested 5 times, and the average value was taken.

[0086] The test results are shown in Tables 1 and 2 below.

[0087] Table 1. Results of thermal aging performance tests: Example 1 32.5 520 88 85 8.2 Example 2 31.2 510 83 79 12.5 Example 3 33.8 505 90 87 5.8 Comparative Example 1 30.5 515 62 55 48.6 Comparative Example 2 31.8 512 75 70 35.2 Comparative Example 3 31.0 508 72 66 10.5 Comparative Example 4 30.2 518 68 62 52.3 Comparative Example 5 30.8 515 73 68 42.8 Comparative Example 6 31.5 510 76 71 45.6 Comparative Example 7 30.6 505 70 64 28.5 Table 2. Results of UV aging performance test: Example 1 91 88 Example 2 86 82 Example 3 93 90 Comparative Example 1 58 52 Comparative Example 2 82 78 Comparative Example 3 80 75 Comparative Example 4 64 58 Comparative Example 5 78 73 Comparative Example 6 80 76 Comparative Example 7 75 69 Results analysis: After thermal aging, the tensile strength retention rate of Examples 1 to 3 was 83 to 90%, the elongation at break retention rate was 79 to 87%, the copper ion content was 5.8 to 12.5 μg / g, and the tensile strength retention rate after ultraviolet aging was 86 to 93%, indicating that the cable sheath material prepared by the present invention has excellent anti-aging properties.

[0088] Comparative Example 1 uses ordinary nano-ZnO instead of hierarchical nano-hybrids. After thermal aging, the tensile strength retention rate is only 62%, and the copper ion content is as high as 48.6 μg / g. Compared with Example 1, the retention rate is reduced by 30% and the copper ion content is increased by 493%. This shows that ordinary nano-ZnO without functionalization modification can neither chelate copper ions nor provide the synergistic effect of LDH layered barrier and ZnO peroxide decomposition.

[0089] Comparative Example 2, which omitted Schiff base functionalization, showed that after thermal aging, the copper ion content increased from 8.2 μg / g to 35.2 μg / g, an increase of 329%, and the tensile strength retention rate decreased from 88% to 75%. This indicates that the deactivation of copper ions in Schiff base is a key link in the quadruple protection system. Without this function, the continuous catalytic oxidation of copper ions leads to the rapid consumption of antioxidants.

[0090] Comparative Example 3, which does not contain ZnO, retains 72% of its tensile strength after thermal aging. Although the copper ion content is low at 10.5 μg / g, indicating that the Schiff base is still chelating copper, the lack of ZnO's catalytic decomposition of peroxides leads to an excessively high rate of free radical chain reaction propagation, which the antioxidant is insufficient to completely intercept.

[0091] Comparative Example 4 used a traditional antioxidant compound formulation, and after heat aging, the tensile strength retention rate was only 68%, with a copper ion content of 52.3 μg / g. This indicates that traditional small-molecule antioxidants cannot cope with the catalytic oxidation of copper ions, and the small molecules migrate and volatilize at high temperatures, leading to a rapid decline in protective effect. Comparative Example 5 used a simple physical mixture to replace the hierarchical structure, and after heat aging, the tensile strength retention rate was 73%, a decrease of 17% compared to 88% in Example 1. This indicates that simple physical mixing cannot achieve the synergistic function of LDH blocking, ZnO catalytic decomposition, and Schiff base chelation; each component functions independently in the matrix and cannot form a positive feedback loop.

[0092] Comparative Example 6 used an antioxidant-supported nano-SiO2 combined with an independent small molecule benzotriazole copper ion deactivator. After heat aging, the tensile strength retention rate was 76%, and the copper ion content was 45.6 μg / g. Compared with Example 1, the retention rate decreased by 14%, and the copper ion content increased by 456%. This indicates that the small molecule benzotriazole migrates and volatilizes severely at a high temperature of 135°C, and cannot provide a lasting copper ion deactivation function. Furthermore, the nano-SiO2 does not have the layered barrier and acid absorption functions of LDH.

[0093] Comparative Example 7 used a small molecule Schiff base to simply blend with ZnO and LDH. After heat aging, the tensile strength retention rate was 70%, and the copper ion content was 28.5 μg / g. Compared with Example 1, the retention rate decreased by 20%, and the copper ion content increased by 248%. This indicates that although the small molecule Schiff base has a certain copper ion chelating ability, it also faces the problem of migration and volatilization at high temperatures. Moreover, the non-anchored Schiff base cannot form a chemical synergy with ZnO and LDH.

[0094] Neither of them can match the overall performance of Example 1, indicating that the hierarchical nano-hybrid design and Schiff base anchoring strategy of the present invention cannot be obtained by simple combination or conventional optimization of existing technologies.

[0095] It is worth noting that the synergistic effect of the quadruple protection feature in Example 1 can be confirmed by the correspondence between copper ion content and mechanical properties: in Comparative Example 2, after the absence of Schiff base, the copper ion content increased sharply from 8.2 μg / g to 35.2 μg / g, while the tensile strength retention rate decreased from 88% to 75%. The increase in copper ion content far exceeded the decrease in mechanical properties, indicating that the catalytic oxidation of copper ions has a nonlinear amplification effect, that is, a small amount of copper ions can generate a large number of free radicals through catalytic cycling, resulting in a disproportionate and sharp decrease in mechanical properties.

[0096] This also explains why simply increasing the amount of antioxidant cannot solve the problem of copper ion catalytic oxidation. In Comparative Example 4, the amount of antioxidant was doubled, but the tensile strength retention rate was still only 68%, because the antioxidant could not prevent copper ions from continuously generating new free radicals.

[0097] Only by chelating inactivated copper ions at the source and combining this with peroxide decomposition and physical barrier can the long-term, high-efficiency anti-aging properties of cable sheaths be achieved.

[0098] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.

Claims

1. An anti-aging cable sheath material, characterized in that, Prepared from the following parts by weight of raw materials: 100 parts of polyether-type thermoplastic polyurethane, Shore hardness 80A to 90A, melt index 15 to 35 g / 10min at 200℃ and 2.16 kg load; Two to six parts of Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids were prepared, wherein the Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids were prepared using ZnAl layered double hydroxide with a Zn to Al molar ratio of 3:1 as a support, ZnO nanoparticles were loaded on the surface of the support, and the surface of the support was modified with γ-aminopropyltriethoxysilane and then reacted with salicylaldehyde to form a Schiff base structure. Hindered phenolic antioxidants 0.3 to 0.8 parts; phosphite antioxidants 0.3 to 0.8 parts; benzotriazole UV absorbers 0.5 to 1.5 parts; carbon black 1 to 3 parts, particle size 20 to 40 nm; zinc stearate 0.3 to 0.8 parts.

2. The anti-aging cable sheath material as described in claim 1, characterized in that: The preparation method of the Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrid includes the following steps: Step A: Dissolve zinc nitrate and aluminum nitrate in deionized water at a Zn to Al molar ratio of 3:1 to prepare a mixed salt solution. Dissolve NaOH and Na2CO3 in deionized water to prepare an alkaline solution. Add the mixed salt solution and the alkaline solution dropwise to the deionized water simultaneously, maintaining a temperature of 60℃ and a pH of 10.0 to 10.

5. After the addition is complete, age the solution at 60℃ for 16 to 20 hours. Filter and wash the solution until the pH of the filtrate is less than 8, and dry it at 80℃ for 10 to 14 hours to obtain ZnAl-LDH. Step B: Disperse ZnAl-LDH in a mixed solvent of ethanol and water, with a volume ratio of ethanol to water of 4:

1. Add zinc acetate dihydrate, with a mass ratio of zinc acetate dihydrate to ZnAl-LDH of 1:2 to 1:

4. Stir at 70°C for 1 to 2 hours, then add NaOH ethanol solution dropwise to make the molar ratio of Zn to OH 1:

2. Continue stirring for 2 to 4 hours, filter, and then heat-treat at 150°C for 2 hours to obtain ZnO / ZnAl-LDH. Step C: Disperse ZnO / ZnAl-LDH in a mixed solvent of ethanol and water, with a volume ratio of ethanol to water of 95:

5. Add γ-aminopropyltriethoxysilane, with the amount of γ-aminopropyltriethoxysilane being 2 to 5% of the mass of ZnO / ZnAl-LDH. Stir at 60°C for 3 to 5 hours. Filter, wash, and dry to obtain amino-modified ZnO / ZnAl-LDH. Step D: Disperse amino-modified ZnO / ZnAl-LDH in anhydrous ethanol, add salicylaldehyde, the mass ratio of salicylaldehyde to amino-modified ZnO / ZnAl-LDH is 1:8 to 1:12, stir at 50℃ for 5 to 7 h, filter and wash, and then vacuum dry at 60℃ for 6 to 10 h to obtain Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids.

3. The anti-aging cable sheath material as described in claim 1, characterized in that: The polyether-type thermoplastic polyurethane is of the polytetrahydrofuran ether diol type, with a number average molecular weight of 80,000 to 120,000.

4. The anti-aging cable sheath material as described in claim 1, characterized in that: The hindered phenolic antioxidant is β-3,5-di-tert-butyl-4-hydroxyphenylpropionate n-octadecyl alcohol ester, the phosphite antioxidant is tris-2,4-di-tert-butylphenyl phosphite ester, and the benzotriazole UV absorber is 2-2H-benzotriazole-2-yl-4,6-di-tert-pentylphenol.

5. The anti-aging cable sheath material as described in claim 1, characterized in that: The anti-aging cable sheath material retains a tensile strength of ≥83% and an elongation at break of ≥80% after heat aging at 135℃ for 168 hours; retains a tensile strength of ≥86% and an elongation at break of ≥82% after UV aging for 500 hours; and has a copper ion content of ≤15μg / g after heat aging at 135℃ for 168 hours.

6. A method for preparing an anti-aging cable sheath material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1: Weigh out the following components according to the specified ratio: polyether thermoplastic polyurethane, Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid, hindered phenolic antioxidant, phosphite antioxidant, benzotriazole UV absorber, carbon black, and zinc stearate. Dry the polyether thermoplastic polyurethane at 80 to 90°C for 3 to 4 hours, and dry the Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid and carbon black at 100 to 110°C for 2 to 3 hours. Step 2: Add the dried polyether thermoplastic polyurethane, Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nano-hybrid, carbon black and zinc stearate into a high-speed mixer and mix at 80 to 90°C and 600 to 800 r / min for 8 to 12 minutes. Then add hindered phenolic antioxidants, phosphite antioxidants and benzotriazole UV absorbers and continue mixing for 5 to 8 minutes to obtain the initial mixture. Step 3: Add the initial mixture to a twin-screw extruder for melt extrusion granulation. The temperature of the twin-screw extruder is 170 to 180℃ in zone 1, 180 to 190℃ in zone 2, 185 to 195℃ in zone 3, 180 to 190℃ in zone 4, and 175 to 185℃ at the die head. The screw speed is 250 to 350 r / min. After water cooling and pelletizing, cable sheath material granules are obtained. Step 4: After drying the cable sheath material granules at 80 to 90°C for 2 to 3 hours, add them to an extruder and extrude them onto the outer surface of the cable conductor at an extrusion temperature of 175 to 195°C. After cooling and shaping, an anti-aging cable sheath is obtained.

7. The preparation method according to claim 6, characterized in that: The Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nanohybrid described in step one is prepared by the following method: Zinc nitrate and aluminum nitrate are dissolved in deionized water at a Zn to Al molar ratio of 3:1 to prepare a mixed salt solution. NaOH and Na2CO3 are dissolved in deionized water to prepare an alkali solution. The mixed salt solution and the alkali solution are simultaneously added dropwise to deionized water while maintaining a temperature of 60℃ and a pH of 10.0 to 10.

5. After the addition is complete, the solution is aged at 60℃ for 16 to 20 hours. The solution is filtered and washed until the pH of the filtrate is less than 8. The solution is then dried at 80℃ for 10 to 14 hours to obtain ZnAl-LDH. ZnAl-LDH was dispersed in a mixed solvent of ethanol and water, zinc acetate dihydrate was added, and the mixture was stirred at 70°C for 1 to 2 hours. Then, NaOH ethanol solution was added dropwise, and the mixture was stirred for another 2 to 4 hours. After filtration, the mixture was heat-treated at 150°C for 2 hours to obtain ZnO / ZnAl-LDH. ZnO / ZnAl-LDH was dispersed in a mixed solvent of ethanol and water, γ-aminopropyltriethoxysilane was added, and the mixture was stirred at 60°C for 3 to 5 hours. After filtration, washing, and drying, amino-modified ZnO / ZnAl-LDH was obtained. Amino-modified ZnO / ZnAl-LDH was dispersed in anhydrous ethanol, salicylaldehyde was added, and the mixture was stirred at 50°C for 5 to 7 hours. After filtration, washing, and vacuum drying at 60°C for 6 to 10 hours, Schiff base-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids were obtained.

8. The preparation method according to claim 6, characterized in that: In step three, the length-to-diameter ratio of the twin-screw extruder is 40:1 to 48:1, and each section of the screw is equipped with kneading blocks to improve the dispersion uniformity of Schiff alkali-functionalized ZnO / ZnAl-LDH hierarchical nanohybrids in polyether-type thermoplastic polyurethane matrix.

9. A cable, characterized in that: The cable includes a conductor and a sheath covering the outer surface of the conductor, the sheath being made of the anti-aging cable sheath material as described in any one of claims 1 to 5.

10. The cable as claimed in claim 9, characterized in that: The cable is used in outdoor wiring scenarios in photovoltaic power stations, wind farms or industrial plants, with a long-term operating temperature of -40 to 105℃ and a service life of ≥25 years.

Citation Information

Patent Citations

  • A kind of heat-resistant and anti-aging cable sheath material and preparation method thereof

    CN103897231B

  • Thermoplastic polyurethane composite materials for cable and optical fiber sheaths and their preparation methods

    CN108003602B